Assessment of butter adulteration practices and associated food safety issues along the supply chain in traditional communities in the central highlands and southwest midlands of Ethiopia - Gemechu, A.T.; Tola, Y.B.; Dejene, T.K.; Grace, Delia; Aleka, F.B.; Ejeta, T.T. (Elsevier, 2021)
Butter adulteration practices and their health risks were assessed along the supply chains in the central highlands and south-western midlands of Ethiopia. Purposive sampling technique was used to select 1101 respondents. Based on the result of the cross-sectional study, fatty acid profiles of butter samples collected from retailers' shops were investigated to determine the extent of adulteration and understand the risks of food safety. The assessment showed that an average of 94% of the respondents were aware about practices of butter adulteration. The common butter adulterants identified include different brands of hydrogenated vegetable oils, Irish potato puree, banana pulps, water, melted tallow, wheat/maize dough, and buttermilk. The practice of adulteration significantly differed (P<0.05) along the supply chain and increased from farm markets to the retail shops. Economically motivated adulteration is the main reason for adulteration and resulted in up to 50 % of butter spoilage. There were significant differences between the fatty acid profiles of pure butter, retailers' butter, pure butter intentionally adulterated with hydrogenated oil, potato puree, and banana pulp, respectively, and pure hydrogenated oil. The presence of methyl oleate, gondoic and eicosadienoic acids in the retailers' butter might be due to adulteration with hydrogenated oils and banana pulps. The study showed the presence of multiple stage adulteration along the supply chain which could endanger the safety and quality of local butter. Policy makers and regulatory bodies in the area can use the information to improve the safety and quality of local butter along the supply chain.